Impact assessment of climate change in Iran using LARS-WG model - Farzanmanesh, Raheleh; Abdullah, Ahmad Makmom; Shakiba, Ali Reza; Amanollahi, Jamil (Universiti Putra Malaysia Press, 2012)

(untitled)
Iran is situated in a very diverse environmental area. The climate of the region is varied and influenced by different patterns. In order to best describe the expected climate change impacts for the region, climate change scenarios and climate variables must be developed on a regional, or even site-specific, scale. The weather generator is one of the valid downscaling methods. In the current study, LARS- WG (a weather generator) and the outputs from ECHO-G for present climate, as well as future time slice of 2010-2039 based on A1 scenario, were used to evaluate LARS-WG as a tool at 13 synoptic stations located in the north and northeast parts of Iran. The results obtained in this study illustrate that LARS-WG has a reasonable capability of simulating the minimum and maximum temperatures and precipitation. In addition, the results showed that the mean precipitation decreased in Semnan, the south of Khorasan and Golestan. Meanwhile, the mean temperature during 2010-2039 would increase by 0.5°C, especially in the cold season.